An interplay between dermatology and ophthalmology: a systematic review and meta-analysis on intense pulsed light therapy for Meibomian gland dysfunction: A systematic review and meta-analysis on intense pulsed light therapy for Meibomian gland dysfunction - Sambhi, Raman-Deep Singh; Sambhi, Gagan Deep Singh; Malvankar-Mehta, Monali (Canadian Journal of Optometry, 2022)
Objectives: To examine the effectiveness of intense pulsed light therapy (IPL) in treating Meibomian gland dysfunction (MGD) and dry eye symptoms. Methods: This study was conducted following the PRISMA statement guidelines. Literature sources included MEDLINE, Embase, Cochrane Library and meeting abstracts from COS and ARVO. Articles underwent 3 stages of screening before data extraction and meta-analysis. Results: 493 studies were found. 50 remained after title screening, 23 after abstract screening and 8 progressed to data extraction. Meta-analysis indicated a significant increase in tear break-up time (TBUT) post-IPL in the less than 1-month follow-up (SMD=1.45; CI:[0.33, 2.57]), 1.5–2 months follow-up (SMD=2.08; CI: [1.14, 3.01]), and 3-months follow-up (SMD=3.28; CI:[2.78, 3.78]) groups and a non-significant increase in TBUT in the 6-month follow-up (SMD=1.90; CI:[-0.18, 3.98]) and at 12-months follow-up (SMD=0.0; CI:[-0.48, 0.48]) groups. Meta-analysis also indicated a significant increase in Schirmer’s test values during the less than 1-month (SMD=0.91; CI:[0.50, 1.31]) and 6-month (SMD=0.65; CI:[0.25, 1.04]) follow-up periods and a non-significant increase in Schirmer’s test values during the 1.5–2 month follow-up period (SMD=0.41; CI:[-0.93, 1.75]). Conclusions: The results suggested a significant increase up to 5-months and a non-significant increase at 6-months post-IPL for TBUT. They also suggested a significant increase in Schirmer’s test values during the less than 1-month and 6-month follow-up periods and a non-significant increase in Schirmer’s test values during the 1-month follow-up period. Ultimately, IPL seems to be a promising therapy for MGD, but we recommend future studies with longer follow-up periods.